Safety and feasibility of laparoscopic liver resection in patients with a history of abdominal surgeries. Issue 8 (August 2020) - Feldbrügge, Linda; Wabitsch, Simon; Benzing, Christian; Krenzien, Felix; Kästner, Anika; Haber, Philipp K.; Atanasov, Georgi; Andreou, Andreas; Öllinger, Robert; Pratschke, Johann; Schmelzle, Moritz
Abstract: Background: Laparoscopic techniques have become the standard approach for most liver resections. Clinical studies providing conclusive evidence which patients benefit most from minimal-invasive surgery remain limited. Methods: We retrospectively analyzed data of all consecutive cases of laparoscopic liver resection between 2015 and 2018 at our center. We compared patients with and without prior abdominal surgeries with respect to postoperative complications (Clavien-Dindo score), length of operation, length of ICU stay and length of hospitalization in univariate and multivariate analyses. Results: Within the study period 319 patients underwent laparoscopic liver resections, 44% of which had a history of abdominal surgeries. Pre-operative characteristics were similar to patients without prior surgeries. Both groups showed comparable rates of post-operative complications (Clavien-Dindo score ≥3a; 12% in patients without vs. 16% with prior surgeries, p = 0, 322). There were no significant differences in length of surgery or length of stay in the ICU or in the hospital. Conclusion: Our data suggest that history of prior abdominal surgery is not a risk factor for post-operative complications after laparoscopic liver resection. We conclude that prior abdominal surgery should not be considered a contra-indication for laparoscopic approach in liver resection.